Design switch mode power supply (SMPS) using pulse width modulation (PWM) controller technique. - Mohd Shahruddin, Harun (2007)
Today, two types of DC power supply can be found in the market, Switch-Mode Power Supply (SMPS) and linear power supply. However, many customers prefer to choose SMPS than linear power supply because for same power rating, SMPS is smaller, cheaper and lighter than linear power supply especially transformer. The high frequency switching transformer that is used in SMPS is smaller and lighter than the transformer that is used in linear power supply. SMPS also have better efficiency than linear power supply. This project is focusing on developing SMPS using flyback converter topology. This flyback converter topology is chosen because it affords to carry power till 150 watts and few components are used to construct the circuit. There is high frequency switching transformer at the middle of flyback circuit that is used to isolate and step-down the high DC voltage and low DC voltage. Only one switching element is used in this flyback topology, normally MOSFET is used as switch. The on and off of the switch is controlled by PWM that generated by PIC microcontroller 16F877A. The on and off of the switch is important because the duty cycles of the PWM is used to regulate the DC output voltage. So the desire output voltage can be produced by generate various duty cycle.